Emerging role of deubiquitination modifications of programmed death-ligand 1 in cancer immunotherapy - Jiang, Yao; Hong, Kai; Zhao, Yingchao; Xu, Kai (Frontiers in Immunology, 2023)
Immune evasion is essential for carcinogenesis and cancer progression. Programmed death-ligand-1 (PD-L1), a critical immune checkpoint molecule, interacts with programmed death receptor-1 (PD-1) on immune cells to suppress anti-tumor immune responses. In the past decade, antibodies targeting PD-1/PD-L1 have tremendously altered cancer treatment paradigms. Post-translational modifications have been reported as key regulators of PD-L1 expression. Among these modifications, ubiquitination and deubiquitination are reversible processes that dynamically control protein degradation and stabilization.Deubiquitinating enzymes (DUBs) are responsible for deubiquitination and have emerged as crucial players in tumor growth, progression, and immune evasion. Recently, studies have highlighted the participation of DUBs in deubiquitinating PD-L1 and modulating its expression. Here, we review the recent developments in deubiquitination modifications of PD-L1 and focus on the underlying mechanisms and effects on anti-tumor immunity.